Augmented motion biofeedback for functional rehabilitation of lower limbs in patients after incomplete spinal cord injury - Schlechtleitner, Matteo (Rehabilitacija (Ljubljana), 2013)
Introduction: The LegTutor device provides visual goniometric feedback of knee flexion and extension. A computerised game incites patients with lower limb impairments to enhance precision of their movement. Methods: Ten patients (9 males; age range 15-70 years) from 5 month to 3 years after incomplete spinal cord injury (C3 to L3; 7 of traumatic cause) were involved in the study. The treatment consisted of 16 LegTutor sessions lasting 45 minutes each, 2 treatments per week for a total of 8 consecutive weeks. The task was to keep a moving target on track. Assessment of motor control (LegTutorTM task score), muscle spasticity (Modified Ashworth Scale), muscle strength (MRC scale) and walking independence (WISCI II) was performed before the beginning and after the end of the treatment. Results: Based on the minimal-real-difference criterion, all the patients improved in the trained task; 5 patients improved by at least 1 raw score point regarding muscle spasticity, 3 regarding muscle strength and 2 regarding walking. The improvement in the task score at each side was correlated with reduced spasticity of the lower limb at the same side (p < 0.05 for Pearson r, Somers d and Cohens kappa). Conclusion: The LegTutorTM treatment appears to increase the ability to voluntarily control the affected lower limb as evidenced by a reduction of spasticity. It could thus be a viable complement to the rehabilitation programs for patients after incomplete spinal cord injury.
Keywords: augmented feedback training; Lower Extremity; poškodbe hrbtenjače; rehabilitacija; rehabilitation; Spinal Cord Injuries; spodnji udi; vadba z nadgrajeno povratno zvezo; vocational rehabilitation